Nonspectroscopic Migratory Cell Monitoring Method Using Retroreflective Janus Microparticles - Kim, Ka Ram; Lee, Danbi; Jeong, Kwan Young; Lee, Kyung Won; Kim, Moon Suk; Kim, Jae Ho; Yoon, Hyun C. (ACS Omega, 2020)
This study aims to suggest a simple migratory cell monitoring method in the Transwell system by utilizing retroreflective Janus microparticles (RJPs) as an optical probe. The RJP could be internalized on cells without compromising the cell viability and can be registered as bright spots within the cell body by inducing retroreflection from nonspectroscopic light sources. Conventional optical probes (e.g., fluorophores, chromogens, and nanoparticles) have been extensively studied and applied across diverse platforms (e.g., Boyden chamber, wound closing, and microfluidic chips) for understanding in vitro kinetic cell behavior. However, the complexities of running such platforms and setting up analytical instruments are limiting. In this regard, we aimed to demonstrate a modified Transwell migration assay by introducing the retroreflection principle to the cell quantification procedures that ensure a simplified optical setup, assure easy signal acquisition, and are compatible with conventional platforms. To demonstrate retroreflection as a signaling principle, a half-metal-coated silica particle that can induce interior retroreflection was synthesized. Because the RJPs can concentrate incident light and reflect it back to the light source, retroreflection was distinctively recognizable and enabled sensitive visualization. To verify the applicability of the developed migration assay, cell quantification during the incremental progress of macrophage migration, and cell quantification under gradients of chemoattractant monocyte protein-1, was accomplished by obtaining phagocytosed RJP-mediated retroreflection signals. Considering that conventional assays are designed as endpoint measurements, we anticipate the proposed retroreflection-based cell quantification technique to be a promising solution, bypassing current limitations.